Perceptions of data processes in mobile-based versus paper-based health information systems for maternal, newborn and child health: a qualitative study in Andhra Pradesh, India. Issue 4 (30th September 2015) - Nguyen, Lillian H; LeFevre, Amnesty E; Jennings, Larissa; Agarwal, Smisha; Mehl, Garrett; Labrique, Alain B; Chava, Lakshmi Durga
Abstract : Background: Many maternal, newborn and child health (MNCH) programmes have paired community health workers with mobile technologies to strengthen the ability of health information systems (HIS) to track women and children across time and beyond the clinical setting. However, little is known regarding the comparative effectiveness of using mobile technologies to enhance HIS data in resource-poor settings. Methods: Focus group discussions were conducted with community health workers called Health Activists (HAs; n=30), Community Organisation Leaders (n=28), HA Trainers (n=21), district and tribal area officials (n=3) and State Officials (n=4). We analysed user perceptions along seven key HIS processes: data collection, transmission, processing, analysis, display, quality checking and feedback. Results: The mobile-based health information system (mHIS) was found to be supportive of the MNCH continuum of care by improving the regularity and timeliness of access to robust data. Respondents noted that data errors were reduced in real time through automated error checking and data processing, which also reduced users' workloads. The mHIS additionally enabled users to analyse both individual and aggregate data, allowing them to identify specific individuals in need of services or training as well as to identify general trends in service delivery. The system's data display and feedback mechanisms were viewed as improving data use for decision-making. The remaining challenges of the mHIS versus the paper-based HIS included resource, infrastructural and technological barriers that hindered efficient use over time. Conclusions: As compared to paper-based HIS systems, mobile technologies can improve health information processes in resource-poor settings. More efforts are needed to ensure sufficient financial investment, training and use of mHIS data at all levels of the HIS.